2014
DOI: 10.15414/jmbfs.2014.4.2.112-116
|View full text |Cite
|
Sign up to set email alerts
|

The Most Important Pollutants of Eastern Slovakia Waters

Abstract: As the area of the Slovak Republic is 49,036 km², there are many potential contaminants that can affect its population. In the socialist era the town of Strážske located in the Košice Municipal Region was the centre of production of polychlorinated biphenyls (PCB) inter alia and nowadays about 3,500 metric tonnes of PCB are persisting there and present the greatest PCB environmental risk in the central Europe. The heavy metal contamination in Slovakia is caused by the natural background as well as by the forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…It was an important gold and mercury mining area for centuries and it can be also the reason for the higher Hg concentration in some samples [33]. Recent monitoring confirmed also strong contamination of surface waters in Spiš with several metals including mercury, copper and lead [34]. Moreover, in this region besides anthropogenic influences also geochemical anomalies are conducive to higher content of heavy metals [25,33].…”
Section: Mercury (Hg)mentioning
confidence: 99%
See 1 more Smart Citation
“…It was an important gold and mercury mining area for centuries and it can be also the reason for the higher Hg concentration in some samples [33]. Recent monitoring confirmed also strong contamination of surface waters in Spiš with several metals including mercury, copper and lead [34]. Moreover, in this region besides anthropogenic influences also geochemical anomalies are conducive to higher content of heavy metals [25,33].…”
Section: Mercury (Hg)mentioning
confidence: 99%
“…The Land Use/Land Cover Area Frame Survey (LUCAS) performed in European Union showed that in more than 95 % of topsoil samples As was detected with concentration below 20 mg/kg and a high portion of samples contain As bellow the limit of detection [33]. In Slovakia, the highest As levels, connected to metal purification industry and fossil fuel combustion, were detected in the Košice region [34].…”
Section: Arsenic (As)mentioning
confidence: 99%
“…During regular monitoring of the Zemplínska Šírava reservoir from 1999 to 2007, high levels of PCB indicator congeners (up to 1633 μg kg −1 dry weight) were measured in bottom sediments 22 . It is assumed that at least 40,000 tons of PCB-contaminated sediments are still present in the reservoir and in the sediments in the waste water canals 23,24 . Even though no recent complex measurements of PCBs in the sediments have been made, we do not assume a significant reduction of the contamination by natural attenuation, as no remediation measures have been implemented yet.…”
Section: Discussionmentioning
confidence: 99%